2016
DOI: 10.1111/inr.12345
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nurses’ perceptions of patient safety culture in psychiatric settings

Abstract: Healthcare managers and policy-makers should encourage educational interventions and help to establish a reporting system that focus on improving systems, not on blaming individuals and encourage open communication among mental healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
10
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
7
10
2
1
Order By: Relevance
“…The PSC dimensions "Teamwork within units," and "Supervisor/ manager expectations & actions regarding patient safety" received the highest scores in both study phases and at both hospitals. This result agrees with what has been reported in other studies (Hamaideh, 2017;Saleh, Darawad, & Al-Hussami, 2015;Vlayen et al, 2015) and indicates that managers seriously consider actions that could improve patient safety. We highlight this finding because forensic nurses have repeatedly expressed a strong desire for transparent and close interaction between managers and staff (Kuosmanen et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The PSC dimensions "Teamwork within units," and "Supervisor/ manager expectations & actions regarding patient safety" received the highest scores in both study phases and at both hospitals. This result agrees with what has been reported in other studies (Hamaideh, 2017;Saleh, Darawad, & Al-Hussami, 2015;Vlayen et al, 2015) and indicates that managers seriously consider actions that could improve patient safety. We highlight this finding because forensic nurses have repeatedly expressed a strong desire for transparent and close interaction between managers and staff (Kuosmanen et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The handout was based on examples of incidents and opportunities for improvement that can also increase staff awareness of patient safety. Effective communication among healthcare professionals is a common, yet critical, method for improving patient safety, as it helps staff prevent and respond to adverse events, as well as give feedback about reported mistakes (Boussat, Bougerol, Detante, Seigneurin, & François, ; Hamaideh, ). However, this requires substantial effort, with the management´s commitment to a culture of safety providing an example for the whole organisation (El‐Jardali et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of other studies are consistent with our findings [4,[29][30][31][32]. For example, the study conducted in Jordan aiming at assessing mental health nurses' perception of patient safety culture in the field of psychiatry demonstrated that two-thirds of nurses assessed patient safety as very good or excellent [29]. Also, the results of the study by Ricklin et al (2019) in Switzerland indicated that patient safety is held to be crucial in this center so that 78% of physicians and 60% of nurses assessed patient safety in the study as very good and excellent [30].…”
Section: Discussionsupporting
confidence: 94%
“…Besides, most participants assessed patient safety as acceptable before intervention whereas they assessed it as very good immediately after and 1 month after educational intervention. The results of other studies are consistent with our findings [4,[29][30][31][32]. For example, the study conducted in Jordan aiming at assessing mental health nurses' perception of patient safety culture in the field of psychiatry demonstrated that two-thirds of nurses assessed patient safety as very good or excellent [29].…”
Section: Discussionsupporting
confidence: 91%